Radon and Neoplasms - Marek Andrzej Komorowski (Toxics, 2023)
Radon is a carcinogenic factor, but the effects of the potential carcinogenicity of radon progeny on the human body during the prenatal period have not yet been explored. Based on data regarding the half-lives of radon-222 and radon-220 and their progeny, this paper considers their potential effects on the human body in the prenatal period. Radon-220 represents a small fraction of the total radon concentration in the air, but the dose of radon-220 progeny may have a significant effect in the prenatal period, as the precursors of polonium-212 exhibit substantially longer half-lives than the corresponding precursors of polonium-214. Theoretically, it is possible that radon-220 decay products, particularly polonium-212, are the predominant emitters of alpha particles in the prenatal period. Studies aiming to establish a relationship between exposure to radon during pregnancy and the subsequently observed incidence of childhood neoplasms should consider this observation.